Comparative analysis of mamushi (Gloydius blomhoffii) bite patients indicates that creatinine kinase levels/white blood cell count trends reflect severity. Issue 2 (27th November 2015) - Okamoto, Osamu; Sato, Seiichi; Sakai, Takashi; Uehara, Miyuki; Takenaka, Ryuichi; Ito, Akiko; Shono, Tomoko; Takeo, Naoko; Ishikawa, Kazushi; Shimizu, Fumiaki; Shimada, Hiromitsu; Hatano, Yutaka; et al.
Abstract : Aim: There has been no indicator that allows an early quantitative evaluation of the severity of a mamushi snake ( G loydius blomhoffii ) bite. Because the number of severe mamushi bite cases is much fewer than non‐severe cases, a formal case–control study is difficult. Therefore, we tried to generate a preliminary quantitative, real‐time index for its severity by referring to published reports of severe mamushi bite cases. Methods: We enrolled patients who presented with a mamushi bite and visited our outpatient clinic. Severe cases were collected from published works. Creatinine kinase levels and white blood cell counts of non‐severe and severe cases were compared and analyzed. Results: There was a lag time of 10 h before the creatinine kinase level began to rise. The speed of the increase was higher in severe cases than in non‐severe cases, and severe cases were recognized as those showing speeds of above 250 IU/L/h. White blood cell counts increased earlier than creatinine kinase levels without any lag time. Severe cases were recognized as those with the counts of over 1, 000 × (h) + 6, 000 [/μL] before 5 h and 300 × (h) + 10, 000 [/μL] after 5 h. Conclusion: We herein present the creatinine kinase level and white blood cell count trends and demonstrate preliminary cut‐off equations. The trends for both parameters serve as quantitative indicators of the severity of a mamushi bite until a large scale case–control study is achieved.